Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T22:31:27+01:00
-0,2 * x + 0,4 +3,6 * (-1/12 ) = -6
-0,2x + 0,4 + 18/5 * (-1/12) = -6
-0,2x + 0,4 - 0,3 = -6
-0,2x + 0,1 = -6 /-0,1
-0,2x = -6,1 /:0,2
-x = -30,5 /*(-1)
x = 30,5

.
2010-03-04T22:33:45+01:00
-0,2x+0,4+36/10*(-1/12)=-6
-0,2x+0,4-3/10=-6
-0,2x=-6-0,4+3/10
-0,2x=-6,4+0,3
-0,2x=-6,1 /:(-0,2)
x=30,5

sprawdzałam kilka razy i wynik jest równy 30,5
2010-03-04T22:53:46+01:00
-0,2 * x + 0,4 + 3,4 * (-1/12)=-6
-0,2x+0,4+3 4/10 * (-1/12)=-6
-2/10x+4/10+34/10*(-1/12)=-6
-2/10x+4/10-17/60=-6
-2/10x=-6-4/10+17/60
-2/10x=-6/1-4/10+17/60
-2/10x=360/60-24/60+17/60
-2/10x=353/60
-2/10x=5,9 /: (-2/10)
x= -29,5